2006
DOI: 10.1097/01.mpa.0000202947.80117.a0
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Evaluation of Stepwise Progression of Pancreatic Carcinoma with Immunohistochemical Analysis of Gastric Epithelial Transcription Factor SOX2

Abstract: The results of our histopathologic examinations suggest that PanIN progresses stepwise to IDC. Immunohistochemistry results suggest that SOX2 is involved in later events of carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(57 citation statements)
references
References 14 publications
0
51
0
1
Order By: Relevance
“…2 It is also noteworthy that USP9X forms protein complexes with SOX2 in multiple cell types, 5,34 a transcription factors whose expression increases during the progression of PDAC. 35 The complexity of assigning a specific role to USP9X in the context of PDAC is further compounded by recent studies indicating that there may be three subtypes of PDAC, as defined by transcriptional profiles. 36 Importantly, these subtypes differ in their clinical outcomes and therapeutic responses, and similar differences may exist between our experimental model and the murine models used previously.…”
Section: Roles Of Usp9x In Pdac Cells Are Context-dependentmentioning
confidence: 99%
“…2 It is also noteworthy that USP9X forms protein complexes with SOX2 in multiple cell types, 5,34 a transcription factors whose expression increases during the progression of PDAC. 35 The complexity of assigning a specific role to USP9X in the context of PDAC is further compounded by recent studies indicating that there may be three subtypes of PDAC, as defined by transcriptional profiles. 36 Importantly, these subtypes differ in their clinical outcomes and therapeutic responses, and similar differences may exist between our experimental model and the murine models used previously.…”
Section: Roles Of Usp9x In Pdac Cells Are Context-dependentmentioning
confidence: 99%
“…Overexpression of SOX2 has been documented in several types of solid tumors (7)(8)(9)(10)(11)(12)(13). Through expression analysis of a panel of breast cancer cell lines and primary tumors, we showed that SOX2 is also overexpressed in human breast cancer tissue and cell lines, and its levels are correlated with tumor grade.…”
Section: Discussionmentioning
confidence: 92%
“…Correlation of SOX2 and Cyclin D1 Expression in Breast Tumor Samples-As stated before, SOX2 is up-regulated in several types of cancers including pancreatic intraepithelial neoplasia, prostate cancer, gastric carcinoma, and breast cancer (7)(8)(9)(10)(11)(12)(13). Analogously, CCND1 amplification/overexpression has been documented in ϳ50% of breast carcinomas (27)(28)(29).…”
Section: Kip1mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of links were recently found between Sox2 and cancer; it has been intensively investigated and was found to contribute to the establishment of lung, prostate and spleen cancer (Saigusa et al, 2009, Sanada et al, 2006, Rodriguez-Pinilla et al, 2007.…”
Section: Sox2mentioning
confidence: 99%